Impact of indirect costs associated with accidents in construction companies - Andueza Navea, Roberto Andrés (2025)
In the construction industry, there are several methodologies that allow estimating the costs of accidents, however, it is necessary to adapt to each country's regulatory reality to reach more accurate values, being able to adapt to the different production scenarios and to the different national realities. This paper presents an analysis of the impact of accident costs using methodology established by the Spanish prevention technical notes NTP 540, 273 Y 594, adjusting them to the Chilean regulations for the calculation of indirect costs of occupational accidents in companies of the construction sector. During 2017-2019, information was collected on the types of accidents occurred in construction sites, considering job position, injured body part, accident agent, values and costs of prevention management, in companies with construction projects of similar characteristics (construction of high-rise building, reinforced concrete construction, between 15 to 20 floors). The application of this tool made it possible to show the values for each type of accident occurring in the companies, with the result that the accident involving the molding operator has the highest cost for the companies. Knowing the cost of the accidents becomes relevant for decision making regarding the preventive management developed in the companies, being able to focus resources in a better way, together with giving a look from the point of view of the operational continuity of the company after the accident.